Legal Obligations of Mining Companies in the Implementation of CSR Based on Laws And Regulations - KMS Herman; Badrunsyah Badrunsyah (Jurnal Indonesia Sosial Teknologi, 2024)
The mining sector plays a crucial role in Indonesia's economy by significantly contributing to national income and employment. However, mining operations can also result in adverse environmental and social impacts. This study aims to examine the legal responsibilities of mining companies in implementing Corporate Social Responsibility (CSR) as stipulated by statutory regulations. PT Bengalon Limestone serves as the case study for this research. Utilizing qualitative research methods with a normative and empirical legal study approach, the data collection method employed is a literature review. Collected data are analyzed through three stages: data reduction, data presentation, and drawing conclusions. The results show that PT Bengalon Limestone has a legal obligation to implement Corporate Social Responsibility (CSR) through several concrete steps. First, the company must carry out the Community Development and Empowerment Program (PPm). In implementing this PPM, PT Bengalon Limestone refers to the Decree of the Minister of Energy and Mineral Resources No. 1824/2018 which includes eight main programs. Furthermore, PT Bengalon Limestone is required to build and maintain public facilities and infrastructure, including road infrastructure which is an important access for the community's economy, and contribute to improving the quality of education and public health. Corporate social and environmental responsibility must be carried out in accordance with applicable legal provisions, including Law No. 25 of 2007, Law No. 40 of 2007, Law No. 4 of 2009, and Government Regulation No. 23 of 2010.